Spatial transcriptome analysis reveals Notch pathway-associated prognostic markers in IDH1 wild-type glioblastoma involving the subventricular zone - Jungk, Christine; Mock, Andreas; Exner, Janina; Geisenberger, Christoph; Warta, Rolf; Capper, David; Abdollahi, Amir; Friauf, Sara; Lahrmann, Bernd; Grabe, Niels; Beckhove, Philipp; Deimling, Andreas von; et al. (BMC medicine, 2016)
The spatial relationship of glioblastoma (GBM) to the subventricular zone (SVZ) is associated with inferior patient survival. However, the underlying molecular phenotype is largely unknown. We interrogated an SVZ-dependent transcriptome and potential location-specific prognostic markers.
Gesehen am 06.05.2020